Role of genetic factors in the pathogenesis of aggressive periodontitis. (June 2014) - Vieira, Alexandre R.; Albandar, Jasim M.
Abstract: This article critically reviews the evidence for a role of genetic factors in the pathogenesis of aggressive periodontitis and discusses the study approaches commonly used to identify genetic risk factors of this disease. Available data suggest that aggressive periodontitis is caused by mutations in multiple genes, combined with environmental effects. Syndromic periodontal diseases include certain monogenic disorders that express phenotypes showing aggressive forms of periodontitis, and the genetic triggering factors of most of these syndromes have been identified. Other periodontal disease phenotypes seem to occur through different genetic predisposition patterns. Case–control and genome‐wide studies have been used to investigate the association with gene polymorphisms. Association studies and the familial aggregation of aggressive periodontitis suggest a significant genetic component in the increased predisposition to this disease. There is evidence to support the contribution of a few major genes or of multiple small‐effects genes. In addition, there is evidence of gene–gene and gene–environment interaction effects. Early studies suggested an X‐linked mode of transmission of aggressive periodontitis, and subsequent studies support an autosomal mode. Genetic studies have the potential to improve the screening programs of subjects at risk for developing aggressive periodontitis and may enhance treatment outcome through gene therapy.